Experimental detection of the penang bridge vibration with real time kinematic GPS - Zulkarnaini Mat Amin, 1961-; Wan Abdul Aziz Wan Mohd. Akib; International Symposium and Exhibition on Geoinformation (2003 : Shah Alam, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
27